2014
DOI: 10.1017/s0022215114001340
|View full text |Cite
|
Sign up to set email alerts
|

Xylitol and its usage in ENT practice

Abstract: Xylitol may be a promising agent for this purpose in ENT practice, but further experimental and clinical studies are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…However, the retention period should probably be too short for S. mutans to ferment indigestible carbohydrates such as FOS, PDX and lactitol in the oral cavity. Indeed, it has been shown that S. mutans rarely degrades indigestible carbohydrates in the oral cavity ( 41 ) . Therefore, indigestible carbohydrates such as FOS, PDX and lactitol would probably not induce dental caries as in a previous study which did not show dental caries formation ( 42 ) .…”
Section: Discussionmentioning
confidence: 99%
“…However, the retention period should probably be too short for S. mutans to ferment indigestible carbohydrates such as FOS, PDX and lactitol in the oral cavity. Indeed, it has been shown that S. mutans rarely degrades indigestible carbohydrates in the oral cavity ( 41 ) . Therefore, indigestible carbohydrates such as FOS, PDX and lactitol would probably not induce dental caries as in a previous study which did not show dental caries formation ( 42 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Xylitol is an inexpensive and sweet tasting sugar alcohol (or polyol), which has been widely used in the food industry to replace sucrose. More recently xylitol has gained popularity for its antimicrobial effects (14,19,20) . Xylitol is thought to exert its antibacterial activity by a number of mechanisms including reduction of the salt concentration of airway surface liquid, repressing bacterial metabolism of glucose to lactate, and disruption of the biofilm extracellular matrix (21)(22)(23)(24)(25) .…”
Section: Discussionmentioning
confidence: 99%
“…terial agent in some countries and has been used in chewing gums, lozenges, syrups, nasal sprays, toothpastes, and mouthwashes. This compound may be a promising agent in ear, nose, throat (ENT) practices, but further experimental and clinical studies are required (13). The antibacterial activities and synergistic effects of xylitol with other sugars have not been clarified yet.…”
Section: Introductionmentioning
confidence: 99%